LEGAL ASSISTANCE TO ENSURE LEGAL CERTAINTY FOR COUPLES IN UNREGISTERED MARRIAGES IN CIREBON - Gusti Yosi Andri; Rd. Handiriono; Djuariah Djuariah; Dharliana Hardjowikarto; Endang Sutrisno; Eni Suhaeni (Ann Publisher, 2026)
Background. Unregistered marriages remain widespread, creating legal issues for both couples and their children. Aims. The objective of this community service program is to provide assistance in the itsbat nikah process at the Religious Court, enabling couples to obtain legal certainty. The implementation methods included socialization, legal counseling, and direct assistance up to the issuance of the court’s decision. Methods. The socialization activities demonstrated an increased awareness among participants regarding the importance of marriage registration. Counseling activities resulted in a deeper understanding of the consequences of marriage. Assistance activities helped participants prepare documents and face the court proceedings. Conclusion. Of the 32 couples who registered, 24 passed the administrative verification to participate in the hearing, and 23 obtained itsbat nikah decrees, while one case was rejected due to age verification issues. Implementation. By obtaining an itsbat nikah decree, couples could proceed to the Office of Religious Affairs to have a marriage certificate issued.